Probleme und Ansätze zur Raumentwicklung in der europäischen Grenzregion Saarland — Lothringen — Luxemburg — Rheinland-Pfalz — Wallonien - Moll, Peter (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
In the border region where Germany, France, Luxembourg and Belgium meet the orientation towards Europe has a long tradition. Even before the term ‘the Europe of the regions’ was coined, institutions were established in this area to foster cross-border co-ordination in representing regional issues in a Europe which was already growing together. It is now a political objective to create a ‘new architecture’ for the partnerships at various levels. The geographical contours for this have yet to be determined, as has the appropriate administrative and decision-making structure. Alongside these issues, one question which arises is that of the status of this region, which sees itself as a major European border-region, vis-á-vis the metropolitan regions in the vicinity in north-western Europe. What problems and lessons does this situation hold for comprehensive regional planning? How can it contribute towards bringing together the various regional interests? How can a balanced development strategy be arrived at for the entire region against the background of the differences in the structures currently in place? This article shows the unique point of departure in this region which calls for customised solutions to be sought and adopted by the co-operating regional partners. ein Modellraum zu sein für eine die Grenzen aufhebende interregionale Kooperation unterhalb der nationalstaatlichen Ebene. Die beteiligten Staaten müssen sich aber einig sein, dies zu wollen. Die einzelnen Regionen würden sich dann untereinander schon verständigen, wie sie ihr kooperatives Netzwerk organisieren müssten. Ein „Interregionaler Rat der Exekutiven im Saar Lorlux-Raum” ist bereits angedancht.